PENGARUH ATTRIBUTES, BENEFITS DAN ATTITUDINAL LOYALTYMEMILIKI DAMPAK TERHADAP BEHAVIORAL LOYALTY PADA FANS PERSIB BANDUNG DALAM INDUSTRI SEPAKBOLA INDONESIA - AULIA DANIBRATA; KLEMENS WEDANAJI PRASASTYO; ALZA ALZA (Media Bisnis, 2020)
The purpose of this study was to determine the effect of attributes, benefits and attitudinal loyalty has a impact on behavioral loyalty in Bandung fans in the Indonesian football industry. This research is expected to be able to improve the results of previous studies.The population of this study came from fans of Persib Bandung who have a domicile in West Java, had watched Persib Bandung directly and had bought Persib Bandung merchandise. The researcher chose 100 respondents as the sample for this study, used insidental sampling as a sampling technique, and used a questionnaire for data collection. This study uses structural equation modeling as a research model. In addition, SPSS and Warp PLS 3.0 are used as statistical tools.The results of this study indicate that attributes and benefits affect attitudinal loyalty, and attitudinal loyalty has an effect on behavioral loyalty.